2005
DOI: 10.1103/physreve.71.041912
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of protein molecules adsorbed at a polyelectrolyte multilayer

Abstract: The spatial distribution of protein molecules interacting with a planar polyelectrolyte multilayer was determined using neutron reflectometry. Staphylococcal nuclease (SNase) was used as model protein that was adsorbed to the multilayer at 22 degrees C and 42 degrees C. At each temperature, the protein solution was adjusted to pD -values of 4.9 and 7.5 to vary the net charge of the protein molecules. The multilayer was built up on a silicon wafer by the deposition of poly(ethylene imine) (PEI), poly(styrene su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…[19][20][21][22] The judicious use of samples organized in a single phospholipid bilayer and of the contrast-variation technique has led to the determination of new structural details on the interaction of polypeptides with membranes. [23][24][25][26][27][28][29][30] In particular, NR is a unique technique to study the distribution of mass along the axis perpendicular to the membrane plane. It allows one to identify the successive layers of chemicals composing the lipid bilayer (lipid headgroups and acyl chains), as well as the compounds embedded in the membrane and located in its vicinity (polypeptide and water molecules, for instance; see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] The judicious use of samples organized in a single phospholipid bilayer and of the contrast-variation technique has led to the determination of new structural details on the interaction of polypeptides with membranes. [23][24][25][26][27][28][29][30] In particular, NR is a unique technique to study the distribution of mass along the axis perpendicular to the membrane plane. It allows one to identify the successive layers of chemicals composing the lipid bilayer (lipid headgroups and acyl chains), as well as the compounds embedded in the membrane and located in its vicinity (polypeptide and water molecules, for instance; see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[95] Recently, the diffusion of Staphylococcal nuclease (SNase) was investigated by neutron reflectometry. [96] It was shown that the SNase is partially penetrating (or diffusing) into a PSS terminating polyelectrolyte multilayer upon adsorption. This penetration is preferred when the positive charge of the protein is high.…”
Section: Diffusion Of Molecules Inserted Into Films (Dyes Growth Facmentioning
confidence: 99%
“…Consequently, these surfaces have great potential for the design of medical devices or implants which are exposed to blood. In recent years the favorable protein adsorption properties of poly(acrylic acid) (PAA) brushes have been reported [74][75][76]. At low salt concentration these polyelectrolyte layers retain proteins in their native state, i.e.…”
Section: Influence Of Surface Properties On Protein Adsorptionmentioning
confidence: 99%